2021
DOI: 10.1021/acsomega.1c00751
|View full text |Cite
|
Sign up to set email alerts
|

Direct Conversion of Syngas to Light Olefins over a ZnCrOx + H-SSZ-13 Bifunctional Catalyst

Abstract: In recent years, bifunctional catalysts for the syngas-to-olefins (STO) reaction via the oxide–zeolite (OX–ZEO) strategy has been intensively investigated. However, the bifunctional catalyst containing H-SSZ-13 with a 100% H + -exchanging degree for the STO reaction has not been developed because of the high selectivity to paraffin. Here, we report a ZnCrO x + H–SSZ-13 bifunctional catalyst, which contains the submicron H–SSZ-13 with adequate acidic strength. L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…A further decrease in the GHSV from 7000 to 4200 mL/g cat h leads to a further increase in methane selectivity to 38%, and a further decrease in C 2 = –C 4 = , C 2 –C 4 paraffin and C 5+ selectivities. The CO conversion at 4200 mL/g cat h was found to be as high as 44%, which is among the highest values reached by OX-ZEO catalysts in the current literature. , , ,,,, The increasing conversion is caused by the higher contact time, which also leads to enhanced hydrogenation of the hydrocarbons. A correlation between GHSV and CO 2 formation was not observed, as for all space velocities tested in this study a CO 2 selectivity of around 42% was observed.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…A further decrease in the GHSV from 7000 to 4200 mL/g cat h leads to a further increase in methane selectivity to 38%, and a further decrease in C 2 = –C 4 = , C 2 –C 4 paraffin and C 5+ selectivities. The CO conversion at 4200 mL/g cat h was found to be as high as 44%, which is among the highest values reached by OX-ZEO catalysts in the current literature. , , ,,,, The increasing conversion is caused by the higher contact time, which also leads to enhanced hydrogenation of the hydrocarbons. A correlation between GHSV and CO 2 formation was not observed, as for all space velocities tested in this study a CO 2 selectivity of around 42% was observed.…”
Section: Resultsmentioning
confidence: 85%
“…One important aspect that could lead to an enhanced understanding is to identify the influence of the metal oxide components on the product distribution. Notably, many OX-ZEO catalysts reported in the literature consist of ZnCr oxides as one catalyst component. ,, For example, Arslan et al obtained a selectivity of 70% for tetramethylbenzene together with a CO conversion of 37% and a CO 2 selectivity of about 50% using a ZnCr 2 O 4 spinel oxide jointly with H-ZSM-5 in a stream of H 2 deficient syngas . Likewise, a combination of SAPO-34 with a series of ZnCr oxides with varying Zn/Cr ratios ranging from 4:1 to 1:3 revealed a significant effect of the metal oxide composition on the OX-ZEO process .…”
Section: Introductionmentioning
confidence: 99%
“…The MeOH can be produced over an industrially applicable Cu/Zn/Al catalyst which is then converted to hydrocarbons over solid acids such as zeolites. However, recent progress in the route converts syngas to hydrocarbons in single-step catalysis, using oxygenated compounds such as MeOH, EtOH, formic acid, etc., as intermediates. , The insights into the different influences of the zeolite topology and acidity can correlate to identify the status quo for future references in catalyst fabrication. Here in this section, we highlight the major characteristics of zeolites that enhance the distinct production of valued products via syngas conversion.…”
Section: Sources Of Syngasmentioning
confidence: 99%
“…To improve further the catalytic performance, a variety of metal oxides have been screened, including single metal component oxides such as ZnO, MnO, Ga 2 O 3 , and CeO 2 , bimetal oxides such as ZnCrO x , ZnAlO x , ZnGaO x , ZnZrO x , ZnMnO x , CeZrO x, and even multimetal oxides. They were combined with various zeolites (zeotypes) such as SAPO-34, SAPO-18, MOR, and SSZ-13 for syngas conversion to light olefins . Among them, zinc–chromium based oxides were demonstrated to be one of the most active oxides so far. , …”
Section: Introductionmentioning
confidence: 99%